Analysis of The Effect of Testimonies, and Brand Image on Buying Decision Variables in The Marketplace Shopee Through Trust as A Moderating Variable - Purwantoro; Aminah, Fitri (Journals of Indonesian Multidisciplinary Research, 2022)
This study aims to determine the effect of testimony, brand image and trust directly on purchasing decisions. The research population is the Rambah Utama community. The number of samples set as many as 100 respondents using the snowball sampling method. As the independent variable in this study is testimonial, brand image which is the moderating variable is trust, and the dependent variable is purchase decision. Data analysis techniques using structural Equating Modeling (SEM PLS) and Smart PLS. The results show that there is a direct influence between testimonials on trust, there is a direct influence between brand image on trust, there is no direct influence between testimonials on purchasing decisions, there is a direct influence between brand image on purchasing decisions, there is a direct influence between trust and purchasing decisions.